Role of cGMP in hydrogen sulfide signaling - Bibli, Sofia-Iris; Yang, Guangdong; Zhou, Zongmin; Wang, Rui; Topouzis, Stavros; Papapetropoulos, Andreas (Nitric oxide, 2015)
•H2S donors and endogenous H2S increase cGMP.•This is achieved by PDE inhibition, eNOS activation or increased NO bioavailability.•H2S is a non-selective PDE inhibitor.•Rate of H2S release determines the concentration of donor needed to increase cGMP.•Donors with faster release rates are more likely to exert their effects through cGMP. The importance of hydrogen sulfide (H2S) in physiology and disease is being increasingly recognized in recent years. Unlike nitric oxide (NO) that signals mainly through soluble guanyl cyclase (sGC)/cGMP, H2S is more promiscuous, affecting multiple pathways. It interacts with ion channels, enzymes, transcription factors and receptors. It was originally reported that H2S does not alter the levels of cyclic nucleotides. More recent publications, however, have shown increases in intracellular cGMP following exposure of cells or tissues to exogenously administered or endogenously produced H2S. Herein, we discuss the evidence for the participation of cGMP in H2S signaling and reconcile the seemingly divergent results presented in the literature on the role of this cyclic nucleotide in the biological actions of H2S.